Evaluating the initial result of transanal and transvaginal NOTES for colorectal cancer - Nhu Hiep Pham; Huu Thien Ho; Anh Vu Pham; Hai Thanh Phan; Thanh Xuan Nguyen; Xuan Dong Pham; Tien Nhan Van; Nghiem Trung Tran; Trung Vy Pham; Si Doan Diem Tran; Trung Hieu Mai; Le Minh Chau Dao (Vietnam Journal of Science, Technology and Engineering, 2017)
Objective: Natural Orifice Transluminal Endoscopic Surgery (NOTES) is an important evolution in minimally invasive surgery (MIS) nowaday. This paper presents the techniques and early results of the pure transanal and transvaginal laparoscopies (NOTES) used for the treatment of colorectal cancer. Material and method: Prospective studies were conducted at Hue Central Hospital, Vietnam. Patients: From December 2013 to September 2015, 22 cololorectal cancer patients (18 rectum, 3 sigmoid tumors and 1 descending colon), adenocarcinoma, T≤ T3N1M0. Methods: The patients were placed in lithotomy and Trendelenburg positions, and the lone-star retractor was placed in the anus (rectum cancer) or vagina (sigmoid cancer). The surgical cavity was then inflated with CO 2 and set at 12 mm/Hg. Dissection was continued until inside of the abdominal cavity (transanal technique). After that, the rectum was pushed into the abdominal cavity. The IMA and IMV were divided (TME included) in both techniques. After finishing dissection, the specimens were pulled out through the anus or vagina to prepare anastomosis. Coloanal and colorectal anastomosis were either hand-sewn (6 cases) or sealed with EEA staplers (16 cases). Results: 2 patients needed one more 5 mm umbilical port in RLQ, 2 patients needed two 5 mm trocars (post radiation hemorrhage, and urethral perforation). One patient converted to open and 1 patient converted to the HYBRID-NOTES procedure. The operation time was 258±40 (190-300) minutes. All patients required minimal analgesia. Bowel movement returned on the first day to 16 patients (average: two days, maximum: three days). The hospital stay was 7±2.8 (4-14) days. Kirwan classification (sphincter function) was very good (stage I: 18). Conclusions: Pure transanal and transvaginal laparoscopies for the treatment of colorectal cancer are feasible and safe. We believe that this is the first pure transvaginal laparoscopy (NOTES) for human in the world. A multicentric study in a large numbers of patients and a long follow-up is necessary.